On building, defending and regulating the self : a psychological perspective - Tesser, Abraham; Wood, Joanne V.; Stapel, Diederik A. (Psychology Press, 2005)
This volume pulls together research on several aspects of the self. One set of chapters deals with the importance of building a self based on authenticity and ""Who I really am.""; a second group deals with the ways in which we defend views of the self as positive and powerful; a third group is concerned with multiple aspects of self regulation. Each of the chapters is a well-written, non-technical description of an important, currently active research program